2023
DOI: 10.1039/d3nr02649c
|View full text |Cite
|
Sign up to set email alerts
|

Ready-to-be-addressed oxo-clusters: individualized, periodically organized and separated from the substrate

Juba Salhi,
Jan Patrick Calupitan,
Michele Mattera
et al.

Abstract: Clusters and oxo-clusters are drawing attention for their amazing physical properties, especially at the scale of the single molecule. However, chemical methods to organize them on a surface in such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…A powerful method for arranging molecules on surfaces is to prefunctionalize the surface with a preorganized template matrix. It was shown that a supramolecular 2D self-assembled network formed as a result of hydrophobic interactions between triazine derivatives with hydrophobic strands serves as an ideal matrix for placing hydrophilic inorganic POMs on the surface of HOPG 215 ( Fig. 9B ).…”
Section: Bioorthogonal Approaches For Surface Engineeringmentioning
confidence: 99%
“…A powerful method for arranging molecules on surfaces is to prefunctionalize the surface with a preorganized template matrix. It was shown that a supramolecular 2D self-assembled network formed as a result of hydrophobic interactions between triazine derivatives with hydrophobic strands serves as an ideal matrix for placing hydrophilic inorganic POMs on the surface of HOPG 215 ( Fig. 9B ).…”
Section: Bioorthogonal Approaches For Surface Engineeringmentioning
confidence: 99%